Freelancers in E-markets: A Role of Social Ties - Денис Олегович Стребков; Андрей Вячеславови Шевчук (Journal of Economic Sociology, 2010)
The study deals with e-markets for self-employed professionals (freelancers). These highly competitive markets emerge in a still weakly regulated cyberspace with virtual interactions. However, market ties between freelancers and their clients are not established as arm’s-length but largely as embedded ties. Social capital of freelancers becomes an effective instrument for ﬁ nding the clients, raising earned income and reducing the moral hazards of opportunism. Empirical data are collected from an online standardized survey of more than 8 thousand freelancers, conducted by the authors in December 2008 at Free-lance.ru.